Dietary fibre intake and its association with inflammatory markers in adolescents. Issue 3 (14th February 2021) - Swann, Olivia G.; Breslin, Monique; Kilpatrick, Michelle; O'Sullivan, Therese A.; Mori, Trevor A.; Beilin, Lawrence J.; Oddy, Wendy H.
Abstract: A high dietary fibre intake has been associated with improvements in inflammatory conditions in adults. However, little is known on whether associations between dietary fibre and inflammation are evident during adolescence. We examined the relationship between dietary fibre intake measured by FFQ and the inflammatory marker high-sensitivity C-reactive protein (hs-CRP) and the adipokines leptin and adiponectin cross-sectionally in 17-year-olds participating in the Raine Study ( n 621). In weighted analysis using tobit and linear regression, and after excluding participants with hs-CRP > 10 mg/l, higher total dietary fibre intake (per 5 g/d) was significantly associated with lower leptin ( β = –0·13, 95 % CI –0·17, –0·09) and adiponectin ( β = –0·28, 95 % CI –0·49, –0·07), but not hs-CRP, in unadjusted analyses. These associations were no longer significant after adjustment for sex, anthropometry and a number of lifestyle factors. However, higher cereal and grain fibre intake was significantly associated with lower leptin ( β = –0·06, 95 % CI –0·10, –0·01) in fully adjusted analysis. Our findings suggest that a higher intake of cereal and grain fibre may contribute to lower leptin in adolescents. This may contribute to reductions in low-grade chronic inflammation and improved health outcomes.